2014
DOI: 10.1016/j.ultsonch.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of sonochemical degradation of ammonium perfluorooctanoate by persulfate oxidant

Abstract: Ammonium perfluorooctanoate (APFO) is an emerging environmental pollutant attracting significant attention due to its global distribution, high persistence, and bioaccumulation properties. The decomposition of APFO in aqueous solution with a combination of persulfate oxidant and ultrasonic irradiation was investigated. The effects of operating parameters, such as ultrasonic power, persulfate concentration, APFO concentration, and initial media pH on APFO degradation were discussed. In the absence of persulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(28 citation statements)
references
References 21 publications
3
23
2
Order By: Relevance
“…The same trend appears to occur for the experiments without temperature control although reaction rates are generally lower for the reasons given in Section 3.2. Other studies have also confirmed the positive effect of increasing SPS concentration on the sonochemical degradation of humic acid [23] and perfluorooctanoic acid [24] although excessive concentrations may have an adverse effect since sulfate radicals can scavenge themselves and/or SPS [25].…”
Section: Effect Of Sps Concentrationmentioning
confidence: 77%
See 2 more Smart Citations
“…The same trend appears to occur for the experiments without temperature control although reaction rates are generally lower for the reasons given in Section 3.2. Other studies have also confirmed the positive effect of increasing SPS concentration on the sonochemical degradation of humic acid [23] and perfluorooctanoic acid [24] although excessive concentrations may have an adverse effect since sulfate radicals can scavenge themselves and/or SPS [25].…”
Section: Effect Of Sps Concentrationmentioning
confidence: 77%
“…Hao et al [25], who studied the sonodegradation of ammonium perfluorooctanoate in the presence of SPS in the pH range 2-13, found that the maximum rate was achieved at pH = 6 but it decreased at lower or higher values.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…As like the H 2 O 2 the PMS and PDS were reported to produce radicals, which will enhance the oxidation reaction (Maruthamuthu and Neta, 1977;Fernandez et al, 2004;Zhao et al, 2010;Chen et al, 2012;Olmez-Hanci and Arslan-Alaton, 2013;Hao et al, 2014). The study of experiments with the additions of PMS and PDS will further increase the degradation efficiency of RB and may enlighten the location of degradation of RB that is in the bulk liquid medium.…”
Section: Effects Of Pms and Pdsmentioning
confidence: 99%
“…Some of these methods additionally utilize hydroxyl radicals to remove pollutants, which have been noted in the literature to be largely inefficient at degrading PFOA due to their relative inactivity [16,17]. Ultrasonic (US) treatment produces micro-plasma via the cavitation phenomenon and is an effective method of destroying organic pollutants and removing PFOA specifically [16,[18][19][20]. This method does not only produce high temperature micro-plasma due to the collapse of tiny vapor bubbles produced by ultrasound, but also leads to in situ pyrolytic reactions in the vapor and interfacial regions of each collapsing bubble resulting in the breakdown of water producing radicals, such as hydroxyl radicals, oxygen atoms and hydrogen atoms [21][22][23].…”
Section: Introductionmentioning
confidence: 99%